Systematic analysis of uncertainty in 2D flood inundation models. (December 2019) - Willis, Thomas; Wright, Nigel; Sleigh, Andrew
Abstract: Assessing uncertainty is a critical part of understanding and developing flood inundation models for use in risk assessment. Typically, uncertainties are investigated by comparing the effects of an ensemble of key model inputs, such as friction values and hydrographic uncertainties, on model outputs. In this study, an approach is adopted that also consider the uncertainty associated with the computational models. Using the LISFLOOD-FP code, which contains multiple methods for solving floodplain flow, two test cases with different hydraulic characteristics are used in a systematic uncertainty analysis. An ensemble of inputs including cell size, hydrological uncertainty, and representation of buildings are assessed for impact on modelling results. Results show the numerical complexity is a significant source of uncertainty in complex flow regimes, but this reduces in typical fluvial flood events. The method of assessing the modelling output is also found to be important in determining the overall influence of parameters. Highlights: This paper analyses the major sources of uncertainty in flood inundation model and evaluates which is the most significant. Two test cases, with different hydraulic properties, are used to provide broader conclusions to the uncertainty analysis. The complexity of the physical model is shown to be highly influential on model results in both test cases. The significance of an input on model outputs is dependent on the assessment method used.